BILINGUAL CURRICULUM MATERIALS SUPPORTING SIGNED LANGUAGE AS A FIRST LANGUAGE FOR DEAF STUDENTS: The integration of technology, learning and teaching - Hoffmeister, Robert J; Karipi, Spyridoula; Kourbetis, Vassilis (Momento - Diálogos em Educação, 2022)
Considering Deaf children and adults as bilingual - their first language is a Signed Language (SL) and the second language is learned via print - provides professionals with a paradigm to be used for creating better learning opportunities. In this paper, Greek Sign Language ((G)SL)) [1] as a first language (L1) is the base language we use to present certain bilingual methodological teaching and learning considerations. This work is the result of a long journey from the initial thinking of the American Sign Language Curriculum and its influence on the development of the (G)SL curriculum in Greece. The paper offers discussion of innovative educational multimedia material that are easily accessed via online web portals, developed for teaching (G)SL as an L1 to pre-school and primary school Deaf children. In this work, SL as L1 is a resource that fully enables Deaf children to learn an L2 via print, supporting their bilingual acquisition capabilities. In developing curricula and supporting materials, we consider two important foundational components: Deaf native signers and near native signers as language role models for Deaf children, parents and teachers; and the development and interaction with digital educational materials. Thus, collaboration between educational and technology professionals and members of the Deaf community is critical. This bilingual model can be incorporated into any SL. (G)SL) is used as a model to display innovative practices merging SL (L1), print (L2), technology and creative instructional and assessment materials, maximized by understanding the visual nature of SL and its advantages for school learning. The penultimate goal is Deaf students to become successful bilingual learners to fully function in the world today and tomorrow. [1] In this paper, we will use (G)SL to indicate that we are discussing Greek Signed Language but content and technology can be used for any SL.